Participation of Women in the Decision-Making Process Vis-À-Vis the Development of Rural Tourism in Mawlynnong Village, Meghalaya - Mukhim, Kular Skhem; Gautam, Punit (Turizam, 2025)
Rural women have a vital role in many parts of community life, but they aren’t usually allowed to be involved in major decisions, or their participation in any decisions is limited. In India, women are key players in tourism, but when it comes to decision making their roles are often restricted. However, in Meghalaya, women are considered and thought to be in good shape and have better autonomy when compared with other women in different parts of the country. The study of the research was conducted in the Mawlynnong village, which is found in Meghalaya. This study investigates women’s engagement in the decision-making process for rural tourism development. The Paper opted for an exploratory study using a field survey and questionnaire. The study’s participants consist of the female residents of the village who are engaged in tourism-related activities. The results show that even though women faced challenges, they were positively involved in decision-making concerning tourism development.